Clinical Utility of Cardiac Magnetic Resonance Imaging in Pericardial Diseases - Aldweib, Nael (Curr Cardiol Rev, 2018)
BACKGROUND: Pericardial diseases are relatively common in clinical practice and encountered in various clinical settings with consequent significant morbidity and mortality. However, the diagnosis as well as management can be complex and challenging, as the clinical presentation is usually non-specific. Therefore, there is an increasing role for Cardiac Magnetic Resonance Imaging (CMR) as an imaging tool to facilitate the diagnosis of pericardial diseases. CONCLUSION: Herein we describe conventional and unique CMR approaches to provide an increased non-invasive understanding of the pericardium in health and disease including a novel method to diagnose constrictive pericarditis via radio-frequency tissue tagging by defining unique visceral-parietal adherence patterns easily learned by the cardiologist and radiologist.